2005
DOI: 10.1007/s10789-005-0202-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanotubular Mg3Si2O5(OH)4-Ni3Si2O5(OH)4 Silicates at Elevated Temperatures and Pressures

Abstract: Mg 3 Si 2 O 5 (OH) 4 -Ni 3 Si 2 O 5 (OH) 4 nanotubes with the chrysotile structure and MgO : NiO molar ratios of 1 : 2 and 2 : 1 are synthesized by hydrothermal reactions at temperatures from 250 to 450 ° C and pressures from 30 to 100 MPa. The reaction path and kinetics, as well as the dimensions and morphology of the resulting nanotubes, are shown to depend on the nature of the starting reagents, chemical composition of the reaction system, and hydrothermal synthesis conditions. At higher nickel concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 3 publications
7
30
2
Order By: Relevance
“…Kinetics of mercury adsorption from waste water using activated carbon has been reported by Mohan et al [11]. In our laboratories [12,13] and literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27] the evaluation of the ion exchange properties of various synthetic inorganic ion exchange materials indicated that, most of inorganic ion exchanger loss its capacities or great extent of its capacities when treated at high temperature. So in this work we attempt to overcome of these problems by thermal treatment of the exchangers in the loaded form at high temperature to construct the material by keeping ionic bonding for exchangeable ions in framework of coordination bonding.…”
Section: Introductionmentioning
confidence: 85%
“…Kinetics of mercury adsorption from waste water using activated carbon has been reported by Mohan et al [11]. In our laboratories [12,13] and literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27] the evaluation of the ion exchange properties of various synthetic inorganic ion exchange materials indicated that, most of inorganic ion exchanger loss its capacities or great extent of its capacities when treated at high temperature. So in this work we attempt to overcome of these problems by thermal treatment of the exchangers in the loaded form at high temperature to construct the material by keeping ionic bonding for exchangeable ions in framework of coordination bonding.…”
Section: Introductionmentioning
confidence: 85%
“…Nickel silicate has been widely studied [13][14][15][16][17] due to its typical layered structure [18] and special properties. The interesting combination of nickel ions and silicate layer structure makes the corresponding nanotube materials rather appealing for various applications like catalysis, controlled release of pharmaceuticals as well as lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, Ni 3 Si 2 O 5 (OH) 4 nanotubes have been successfully prepared. For example, Korytkova et al [15,16] prepared a pure phase of Ni 3 Si 2 O 5 (OH) 4 nanotubes using NiSiO 3 and Ni(OH) 2 as precursors at high temperature (400 °C ) and pressure (70 MPa) for more than 8 h. McDonald et al [17] found that the Ni 3 Si 2 O 5 (OH) 4 nanotubes could be obtained at a lower temperature of 250 °C in 18 h using NiCl 2 ·6H 2 O and silicic acid as precursors; however, the precursors must be first stirred for 3 days under a nitrogen atmosphere and then reacted in argon. The reported procedures are thus rather energy-and time-consuming and difficult to realize on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these substitutive impurities in chrysotile, even to a limited extent, affects its morphology and chemical/physical properties [3,[9][10][11] and it also could play an important role in pathological effects. Infact several authors attribute the chrysotile noxiousness to its morphology and chemical composition [12,13].…”
Section: Introductionmentioning
confidence: 99%